2019
DOI: 10.1038/s41598-019-45550-z
|View full text |Cite
|
Sign up to set email alerts
|

Dual β-lactam combination therapy for multi-drug resistant Pseudomonas aeruginosa infection: enhanced efficacy in vivo and comparison with monotherapies of penicillin-binding protein inhibition

Abstract: The aim of the study was to determine the efficacy of dual β-lactam combination treatments derived from eight approved drugs against Galleria mellonella larvae infected with MDR strains of P . aeruginosa . Carbapenem-resistant P . aeruginosa NCTC 13437 and an unrelated clinical isolate were used to infect G . mellonella larvae and the efficacy of twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 51 publications
0
21
1
Order By: Relevance
“…The combination of a carbapenem antibiotic with colistin increased the eradication of P. aeruginosa infections [42]. Dual β-lactam therapy also has been shown to have enhanced efficacy in killing P. aeruginosa [119], with an example being ceftazidime-avibactam paired with meropenem [120].…”
Section: β-Lactam Antibiotics: Inhibitors Of Pbpsmentioning
confidence: 99%
“…The combination of a carbapenem antibiotic with colistin increased the eradication of P. aeruginosa infections [42]. Dual β-lactam therapy also has been shown to have enhanced efficacy in killing P. aeruginosa [119], with an example being ceftazidime-avibactam paired with meropenem [120].…”
Section: β-Lactam Antibiotics: Inhibitors Of Pbpsmentioning
confidence: 99%
“… 10 , 90 Against non-MBL P. aeruginosa , in vitro studies have shown synergistic activity for combinations of piperacillin and a third-generation cephalosporin, piperacillin and cefepime, ceftazidime and meropenem, and ceftazidime/avibactam and meropenem, whereas synergistic activity against MBL P. aeruginosa has been shown for the combination of aztreonam and ceftazidime/avibactam. 10 , 87 , 91 94 Further, the combination of aztreonam and piperacillin/tazobactam has been shown to result in antagonism against P. aeruginosa . 10 , 95 Additionally, combinations of meropenem and ampicillin/sulbactam and of imipenem plus ampicillin/sulbactam have been shown to have synergistic activity against CRAB.…”
Section: Reviewmentioning
confidence: 99%
“…Nano-penicillin ( Yariv et al, 2015 ) or nano-ampicillin can be introduced to fight drug-resistant Streptococcus pneumoniae . Combinatorial beta-lactams ( Siriyong et al, 2019 ) synthesized in pure-nano form as explained in ( Yariv et al, 2015 ) may be applied to address multi-drug resistant Pseudomonas aeruginosa .…”
Section: Future Research Perspectivesmentioning
confidence: 99%